Assembly and Characterization of gp160-Nanodiscs: A New Platform for Biochemical Characterization of HIV Envelope Spikes - Nakatani-Webster, Eri (J Virol Methods, 2015)
The human immunodeficiency virus (HIV) is the causative agent of acquired immune deficiency syndrome (AIDS) and is thus responsible for significant morbidity and mortality worldwide. Despite considerable effort, preparation of an effective vaccine for AIDS has been elusive and it has become clear that a fundamental understanding of the relevant antigenic targets on HIV is essential. The Env trimer spike is the only viral antigen present on the surface of the viral particle and it is the target of all broadly neutralizing antibodies isolated to date. Thus, a soluble, homogeneous, and well-defined preparation of Env trimers is an important first step towards biochemical and structural characterization of the antigenic spike. Phospholipid bilayer nanodiscs represent a relatively new technology that can serve as a platform for the assembly of membrane proteins into a native membrane-like environment. Here we describe the preparation and characterization of unprocessed full-length, natively glycoslyated gp160 Env proteins incorporated into nanodiscs (gp160-ND). The particles are soluble and well defined in the absence of detergent, and possess a morphology anticipated of Env incorporated into a lipid ND. Importantly, the gp160-NDs retain CD4 and Env antibody binding characteristics expected of a functional trimer spike and their incorporation into a lipid membrane allows interrogation of epitopes associated with the membrane-proximal ectodomain region of gp41. These studies provide the groundwork for the use of gp160-ND in more detailed biochemical and structural studies that may set the stage for their use in vaccine development.